Las ideas pedagógicas de Tolstoi y Tagore en el proyecto vasconcelista de educación, 1921-1964 - Moraga Valle, Fabio (El Colegio de México, A.C., 2016)
According to the history of education in Mexico, as of 1920, there were two dissimilar ideological influences on the country’s educational system: “the Russian example” and “the pedagogy of Dewey.” These interpretations have not taken into account the fact that the educational project spearheaded by the philosopher José Vasconcelos was not exactly inspired in the Soviet model and was downright hostile to any influence from the United States. This article analyzes two ideological sources that were key for the “Vasconcelosian educational project”: the pedagogical thought of the Russian anarchist writer Leo Tolstoy and the Bengali poet and artist Rabindranath Tagore. The influence of these ideological sources can be traced up to the 1960s.